Effects of Thermostable Phytase Supplementation on the Growth Performance and Nutrient Digestibility of Broilers - Chen, Y.P.; Duan, W.G.; Wang, L.L.; Zhang, S.L.; Zhou , Y.M. (International Journal of Poultry Science, 2013)
A study was conducted to investigate the effects of thermostable phytase supplementation on the growth performance and nutrient digestibility of broilers for 42 d. 1-day-old Arbor Acres chicks with similar initial body weight were randomly divided into 3 treatments consisting 6 pens of 20 chicks per pen. The control group was given maize-soybean meal basal diet and the other two groups were fed the basal diet including either 500 U ordinary phytase/kg diet or 500 U thermostable phytase/kg diet. The results indicated that broilers given diets supplemented with thermostable phytase have increased body weight, body weight gain and feed intake than these fed basal diet (p